Malnutrisi rumah sakit dan asuhan nutrisi pediatrik di Rumah Sakit Hasan Sadikin Bandung - Tisnasari Hafsah; Titis Prawitasari; Julistio Tryoga Budhiawan Djais (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2019)
Hospital malnutrition and pediatric nutrition care in Hasan Sadikin Hospital BandungBackground: Malnutrition during hospitalization delays the recovery of children with acute or chronic illnesses. The Pediatric Nutrition Care (PNC) can improve nutritional support and reduce the prevalence of hospital malnutrition.Objectives: This study was done to find evidence of hospital malnutrition and to evaluate the nutrition care in the pediatric ward of Dr. Hasan Sadikin Hospital, Bandung. Methods: We evaluated malnutrition by comparing body weight change between the first day of admission and at hospital discharge to the length of hospitalization. Screening for malnutrition risk was done using modified Pediatric Yorkhill Malnutrition Screening (mPYMS). Score≥2 was determined as high risk. The PNC process was evaluated by a focused group discussion with PNC-associated pediatric ward personnel.Results: From February-March 2016, 760 patients were admitted to the pediatric ward, of which 111(14.6%) were included in the study. An mPYMS score of ≥2 was found in 69(62.2%) of the patients. During hospitalization, body weight decreased in 23(20.7%) patients, 10(9.0%) of whom were defined as hospital malnutrition. Among these, seven had an mPYMS score≥2. PNC was performed in patients with an mPYMS score≥2 by dietitians who also provided a standardized nutrition care process following American Dietetic Association recommendation. However, a dedicated multidisciplinary PNC team was absent and the nutrition and metabolic disease division was consulted only in a few cases. Performing consistent monitoring and evaluation of PNC was also found to be difficult. Conclusions: Hospital malnutrition may be prevalent among pediatric patients in Dr. Hasan Sadikin Hospital, Bandung. Improving PNC services may reduce this prevalence.